Reformulation of The Post-Pandemic Learning System in Responding the Challenges of Lost Learning and Lost Generation - Kasman, Kasman; Nasution, Marlian Arif; Rahmat, Paisal; Wahyudi, Ade Arga (Jurnal Paedagogy, 2024)
This study aims to reformulate the post-pandemic learning system at UIN Imam Bonjol and UIN Syekh Ali Hasan Ahmad Addari in responding to the challenges of lost learning and lost generation. This research used a qualitative approach with a multi-case study method. Participants in this study were selected by purposive sampling, namely institutional field, and academic leaders, LPM, lecturers and students. Data collection techniques using focus group discussions and interviews. The data analysis technique was carried out with individual and cross-case analyses. The research findings stated that the pandemic affected the learning system, for example, through changes in student attitudes, low motivation in learning, readiness of teaching materials, limited ability to use technology, and network disruption. Policies related to the implementation of distance learning bring challenges that must be faced by UIN Imam Bonjol and UIN Syahada, including determining learning goals, adapting the learning system, adjusting the characteristics of lecturers and students, as well as the need for learning facilities. UIN Imam Bonjol and UIN Syahada reformulated the learning system by implementing the hybrid learning system to anticipate the occurrence of lost learning. Lecturers and students responded positively to the new learning system policy, in line with the benefits obtained, for example, flexibility in learning, students are used to self-study, digital-based learning materials, still respect face-to-face learning, flipped learning innovation, curriculum appropriate to the industrial era 4.0, and the implementation of an independent curriculum.